How does climate policy affect technical change? An analysis of the direction and pace of technical progress in a climate-economy model - Lea Nicita; Carlo Carraro; Emanuele Massetti (Fondazione Eni Enrico Mattei (FEEM), 2009)
This paper analyses whether and how a climate policy designed to stabilize greenhouse gases in the atmosphere is likely to change the direction and pace of technical progress. The analysis is performed using an upgraded version of WITCH, a dynamic integrated regional model of the world economy. In this version, a non-energy R&D Sector, which enhances the productivity of the capital-labor aggregate, has been added to the energy R&D sector included in the original WITCH model. We find that, as a consequence of climate policy, R&D is re-directed towards energy knowledge. Nonetheless, total R&D investments decrease, due to a more than proportional contraction of non-energy R&D. Indeed, when non-energy and energy inputs are weakly substitutable, the overall contraction of the economic activity associated with a climate policy induces a decline in total R&D investments. However, enhanced investments in energy R&D and in the energy sector are found not to crowd-out investments in non-energy R&D.
Keywords: C72; H23; Q25; Q28; 330; Technical Change; Climate Policy; Stabilization Cost; R&D Investments